Acceptance of COVID-19 Booster Dose 3 Based on the Health Belief Model: A Study at Peureulak Public Health Center - Emira, Ezi; Solikhah, Solikhah; Nur Djannah, Sitti; Cahyarani, Astika; Ximenes, Adriano; Farah Az Zahra, Fauzia Farah Az Zahra; Febriyanto, Kresna (Universitas Ahmad Dahlan, 2025)
Background: The COVID-19 vaccination program faces significant challenges due to public hesitation, with some individuals rejecting or harboring doubts across the 34 provinces of Indonesia. The Health Belief Model, one of the most widely used theories for understanding health and illness behaviors, provides a framework for examining participants' perceptions of susceptibility, severity, benefits, barriers, self-efficacy, and cues to action regarding COVID-19 vaccination. This study aimed to assess the acceptance of the third dose of the COVID-19 vaccine (Booster) using the Health Belief Model at Peureulak Public Health Center, East Aceh. Method: This research was conducted at the Peureulak Health Center, East Aceh. and employed an analytical quantitative approach with a cross-sectional design, involving 394 participants selected through purposive sampling. Data analysis methods applied include univariate, bivariate, and multivariate. Result: Results showed a significant association between perceived susceptibility and vaccine acceptance, particularly concerning infection risk. However, no significant relationship was identified between perceived severity and acceptance. Perceived benefits, in the terms of the belief that vaccination could reduce the risk of infection or complications and alleviate concerns about COVID-19 were strongly associated with vaccine acceptance. Perceived barriers were also significantly related to vaccine acceptance, especially regarding concerns over potential side effects. Additionally, cues to action, such as adequate information about COVID-19 and vaccination, positively contributed to increased vaccine acceptance. Conclusion: perceived susceptibility, perceived benefits, perceived barriers, and cues to action were significantly related to vaccine acceptance.